Transformaciones judiciales en el Ecuador: El equilibrio de poderes visto a través del análisis de redes sociales - Efrén Ernesto Guerrero (Ius Humani. Jornal do direito, 2014)
This text explores the balance of powers in the Republic of Ecuador through Social Network Analysis (SNA). It argues that formal and informal ties among political system’s actors can be affected as a result of an improvement action within a part of the State. The Article recounts three essential elements: the theoretical apparatus of the balance of power in the State, a summary of the reform actions in the Ecuadorian juridical system, and an analytical contrast between governance models of the Ecuadorian State after the reform of the judiciary, conducted between 2010 and 2014. For this purpose, a comparison of the models of balance by using social network analysis is proposed; thereof a series of statistics that will show the possibility of changes in the capabilities of horizontal accountability of the Judiciary are obtained. This data show an evidence base that small changes in the fabric of government relations have extensive quantitative consequences on the balance of powers, and appear as heuristics of change in the dynamics of political power. It concludes indicating that reforms of the judicial system have created a more efficient system but, according to the obtained data, centrality of power can generate unwanted effects in public administration and in the structure of power control of the State.